PERLINDUNGAN HUKUM SAKSI DAN KORBAN DALAM PROSES PERKARA PIDANA DI PENGADILAN - Hardijanto, Heru Purwadi (Universitas Slamet Riyadi, 2012)
Abstract:Law formulation of protection eyewitness is law phenomenon crime system in theIndonesia as crime system of judicature, where as law straightening of alwayscorrelation by law enforcer. Law straightening in eyewitness protection has been foundthat often witnesses do not get protection law and even become accused. As that way informulation wisdom punish about eyewitness protection and it needed in future withlaw balance such as KUHP, it form in unity law system, so easy to do law. Law ofprotection of eyewitness and victim and is new masterpiece of nation in the Indonesiawhich inspiring a law aspiration protecting the whole Indonesian nation especiallyeyewitness rights and victim in course of criminal justice. So that thereby punishprotection of victim and eyewitness represent guidance in conducting criminal lawformulation in one standard law system that is in a formulation punish Indonesia crimesystem of judicature.Key words: protection punish victim and eyewitness, process criminal justice.